Detection of multidrug-resistant Acinetobacter baumannii by metagenomic next-generation sequencing in central nervous system infection after neurosurgery: A case report - Tian, Ying; Xia, Han; Zhang, Linlin; Zhou, Jian-Xin (Frontiers in Public Health, 2022)
Background Central nervous system (CNS) infection is one of the most serious complications after neurosurgery. Traditional clinical methods are difficult to diagnose the pathogen of intracranial infection. Due to recent advances in genomic approaches, especially sequencing technologies, metagenomic next-generation sequencing (mNGS) has been applied in many research and clinical settings. Case presentation Here, we report a case of CNS infection with Acinetobacter baumannii in a 15-year-old woman, who previously underwent surgery for recurrence of ependymoma in the fourth ventricle. On the eleventh postoperative day, the patient had a high fever and leukocytosis in the cerebrospinal fluid (CSF). mNGS using CSF rapidly and accurately identified the causative pathogen as A. baumannii with carbapenem resistance genes blaOXA-23 and blaOXA-51, which were confirmed by subsequent culture and susceptibility tests within 5 days. During the disease, mNGS, culture, and drug susceptibility testing were continued to monitor changes in pathogenic bacteria and adjust medication. At present, there are no case reports on to the use of mNGS for detecting pathogens in postoperative infection with ependymoma and guide medication. Conclusion mNGS has great advantages in pathogen identification and even pathogen resistance prediction. Multiple mNGS examinations during the course of the disease play an important role in the dynamic monitoring of pathogens.